2013
DOI: 10.1016/j.combustflame.2013.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic centers in particulate formed from the oxidative pyrolysis of 1-methylnaphthalene in the presence of Fe(III)2O3 nanoparticles

Abstract: The identity of radical species associated with particulate formed from the oxidative pyrolysis of 1-methylnaphthalene (1-MN) was investigated using low temperature matrix isolation electron paramagnetic resonance spectroscopy (LTMI-EPR), a specialized technique that provided a method of sampling and analysis of the gas-phase paramagnetic components. A superimposed EPR signal was identified to be a mixture of organic radicals (carbon and oxygen-centered) and soot. The carbon-centered radicals were identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…The detected EPR spectra present a simple singlet line (Figure a, inset spectra) with low g-values (from 2.0031 to 2.0034) and a relatively narrow spectrum with Δ H p‑p in the range of 4.9–5.8 G (Figure b) characteristic most probably to carbon centered radicals. Similar radicals (identified as soot radicals) were reported in our earlier publication . Formation of soot is typical during lignin low temperature and longtime pyrolysis and is reported as coke formation .…”
Section: Results and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The detected EPR spectra present a simple singlet line (Figure a, inset spectra) with low g-values (from 2.0031 to 2.0034) and a relatively narrow spectrum with Δ H p‑p in the range of 4.9–5.8 G (Figure b) characteristic most probably to carbon centered radicals. Similar radicals (identified as soot radicals) were reported in our earlier publication . Formation of soot is typical during lignin low temperature and longtime pyrolysis and is reported as coke formation .…”
Section: Results and Discussionsupporting
confidence: 87%
“…Similar radicals (identified as soot radicals) were reported in our earlier publication. 53 Formation of soot is typical during lignin low temperature and longtime pyrolysis and is reported as coke formation. 54 In fact, the secondary processes (condensation/polymerization) occur in the gas phase 16 as well as on the surface of residue from lignin pyrolysis producing coke/soot particles with characteristic EPR spectra, Figure 4a (inset spectra).…”
Section: Resultsmentioning
confidence: 99%
“…The spectra of the coking sample with added Fe 3+ contained a signal with a very wide half-width, which is different from the signal in the spectrum of coked glucose alone; however, this effect is not clear. Previous studies have shown that the formation of EPFRs from the oxidative pyrolysis of 1-methylnaphthalene can be promoted by the addition of Fe 2 O 3 nanoparticles in a reaction system that contains Fe 2 O 3 nanoparticles and gas organic molecules in a flow reaction tube and an oxygen atmosphere; 51,52 this study, the pyrolysis of the mixture of glucose and Fe 2 (SO 4 ) 3 solutions occurred in an oxygen-free atmosphere. Soluble metal ions had an inhibitory effect on EPFR formation.…”
Section: Environmental Science and Technologymentioning
confidence: 68%
“…Both line types were narrower than the line widths of radicals obtained for carbon black (23e66 G) [75]. The ESR signal of pyrolyzed lignocellulosic materials is often only a broad featureless singlet without the hyperfine splitting which is caused by the presence of multiple radical species or strong matrix interaction occurred between the products [76]. In addition, the heterogeneity of biomass samples and that the radicals are not exclusively centered on single atoms could lead to broad featureless singlets, as reported by Herring et al [76].…”
Section: Discussionmentioning
confidence: 78%
“…The ESR signal of pyrolyzed lignocellulosic materials is often only a broad featureless singlet without the hyperfine splitting which is caused by the presence of multiple radical species or strong matrix interaction occurred between the products [76]. In addition, the heterogeneity of biomass samples and that the radicals are not exclusively centered on single atoms could lead to broad featureless singlets, as reported by Herring et al [76]. Investigations of Ross et al [77] showed that the differences in line widths were caused by the formation of the disorganized carbon with unpaired electrons (narrow signal) and organized carbon with the conductive electrons (broad signal).…”
Section: Discussionmentioning
confidence: 99%